PKC inhibition results in a Kv1.5 + Kvβ1.3 pharmacology closer to Kv1.5 channels. (5th September 2014) - Macías, A; de la Cruz, A; Prieto, A; Peraza, D A; Tamkun, M M; González, T; Valenzuela, C
<x xml:space="preserve">Abstract</x> Background and Purpose The Kvβ1.3 subunit modifies the gating and pharmacology of Kv1.5 channels in a PKC‐dependent manner, decreasing channel sensitivity to bupivacaine‐ and quinidine‐mediated blockade. Cardiac Kv1.5 channels associate with receptor for activated C kinase 1 (RACK1), the Kvβ1.3 subunit and different PKC isoforms, resulting in the formation of a functional channelosome. The aim of the present study was to investigate the effects of PKC inhibition on bupivacaine and quinidine block of Kv1.5 + Kvβ1.3 channels. Experimental Approach HEK293 cells were transfected with Kv1.5 + Kvβ1.3 channels, and currents were recorded using the whole‐cell configuration of the patch‐clamp technique. PKC inhibition was achieved by incubating the cells with either calphostin C or bisindolylmaleimide II and the effects of bupivacaine and quinidine were analysed. Key Results The voltage‐dependent inactivation of Kv1.5 + Kvβ1.3 channels and their pharmacological behaviour after PKC inhibition with calphostin C were similar to those displayed by Kv1.5 channels alone. Indeed, the IC50 values for bupivacaine were similar in cells whose PKC was inhibited with calphostin C or bisindolylmaleimide II. Similar results were also observed in the presence of quinidine. Conclusions and Implications The finding that the voltage‐dependence of inactivation and the pharmacology of Kv1.5 + Kvβ1.3 channels after PKC inhibition resembled that observed in Kv1.5 channels suggests that both processes are dependent on PKC‐mediated phosphorylation. These results may have clinical relevance in diseases that are characterized by alterations in kinase activity.